2018
DOI: 10.1002/hec.3659
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the legalisation of abortion on birth outcomes in Uruguay

Abstract: This study investigates the short-term impact on the quantity and quality of births of an abortion reform in Uruguay that legalised termination of pregnancy until the 12 week of pregnancy in the short run. We employ a differences-in-differences approach, comprehensive administrative records of births, and a novel identification strategy based on the planned or unplanned nature of pregnancies that came to term. Our results suggest that this policy change has led to an 8% decline in the number of births from unp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 53 publications
1
32
0
Order By: Relevance
“…Three studies explored the effect of abortion legalization on adolescent pregnancy. They found legalization did not reduce childbearing among adolescents in the three years after its adoption in Mexico City ( 42 ), although the findings are mixed in Uruguay ( 43 , 44 ). Comparing 2010 with 2014 adolescent fertility data from health centers in Montevideo one study found no effect of abortion legalization upon adolescent pregnancy nor fertility rates ( 43 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies explored the effect of abortion legalization on adolescent pregnancy. They found legalization did not reduce childbearing among adolescents in the three years after its adoption in Mexico City ( 42 ), although the findings are mixed in Uruguay ( 43 , 44 ). Comparing 2010 with 2014 adolescent fertility data from health centers in Montevideo one study found no effect of abortion legalization upon adolescent pregnancy nor fertility rates ( 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…They found legalization did not reduce childbearing among adolescents in the three years after its adoption in Mexico City ( 42 ), although the findings are mixed in Uruguay ( 43 , 44 ). Comparing 2010 with 2014 adolescent fertility data from health centers in Montevideo one study found no effect of abortion legalization upon adolescent pregnancy nor fertility rates ( 43 ). However, a later study comparing national data from 2006 and 2012, found access to legal abortion correlated with reduced adolescent fertility ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…The VTP law has produced neither significant changes in total births, nor significant changes  in the number of abortions among teenagers. 4 This legislation did produce a reduction in the number of unplanned pregnancies of about 8 percent, but did not produce any effect on adolescent fertility (López Gómez, Brunet, and Couto 2019;Antón, Ferre, andTriunfo 2018, 2016).…”
Section: Program Features and Contraceptive Methods In Uruguaymentioning
confidence: 99%
“…The quarterly effects have similar figures and trends (see Online FigureA4). 15Antón, Ferre, and Triunfo (2018) found that the Voluntary Termination Law reduced by 8 percent unplanned pregnancy among more educated mothers between 20 and 34 years old and improved pregnancy quality.…”
mentioning
confidence: 99%
“…Manuscripts described data from the following settings: Argentina [ 13 ], Australia [ 14 18 ], Chile [ 19 , 20 ], Colombia [ 21 23 ], Ethiopia [ 24 ], Ghana [ 25 ], Ireland [ 26 , 27 ], Mexico [ 23 , 28 ], Rwanda [ 29 , 30 ], Thailand [ 31 ], United Kingdom/Great Britain [ 23 , 32 ], and Uruguay [ 33 ]. The characteristics of included manuscripts are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%